PENGARUH INDEPENDENSI, ETIKA AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT AKUNTAN PUBLIK DI KALIMANTAN TIMUR (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2018)
Mita Pranata Munthe.2018.The Influence of Independency, Audit Ethics, and Audit Fee to Audit Quality of Public Accountant In East Kalimantan. Supervised by Dr. Cornelius Rantelangi, S.E., M.M., Ak.,CA.,BKP and Mr. Agus Iwan Kesuma, S.E.,M.A . This research purposed to examine the influence of independency, audit ethics and audit fee to audit quality of public accountant. The type of this research is descriptive qualitative with primary data source which is questionnaire technique. The technique of the sampling is purposive sampling with amounts of the sample are 71 respondents. The analysis technique of this research is multiple linear regression analysis with the equation of regression Y = 14,601 + 0,291X1 + 0,550X2 + 0,202X3.. In this research conducted data quality test, classical assumption test and hypothesis test either partially or simultaneously with significance level (?) is 0,050 (5%). The result of this research obtained number of statistical significance (Sig.) for independency, audit ethics, and audit Fee are 0,003; 0,000; and 0,027 which the values of statistical significance are smaller than the value of significance test (?) (Sig. < 0,05). From this research can be concluded that independency, audit ethics, and audit fee affect positively and significantly toward audit quality of public accountant in east Kalimantan either partially or simultaneously Keywords : Independency, Audit Ethics, Audit Fee and Audit Quality